An unexpected role for FosB in activation-induced cell death of T cells - Baumann, Sven; Angel, Peter; Krammer, Peter H. (Oncogene, 2003)
The CD95 (APO-1/Fas) system plays a major role in induction of apoptosis in lymphoid and nonlymphoid tissues. The CD95 (APO-1/Fas) ligand (CD95L) is induced in response to a variety of signals including TCR/CD3 stimulation or application of chemotherapeutic drugs. Here we report that an AP-1 site located in the 5′ untranslated region of the CD95L gene is required for TCR/CD3-mediated induction of the human CD95L promoter. Electrophoretic mobility shift assays using nuclear extracts of Jurkat T cells as well as TCR/CD3-restimulated primary human T cells demonstrated specific binding of AP-1, predominantly composed of c-Jun and FosB, to this sequence. Ectopic expression of transdominant negative Jun mutants strongly reduced CD95L promoter activity and activation-induced cell death (AICD), confirming the functional significance of FosB/c-Jun binding. Thus, our results demonstrate an important novel function for FosB dimerized with c-Jun in TCR/CD3-mediated AICD in human T cells.
Gesehen am 14.04.2021